SUITABLE LOCAL MEDIA AND OPERATION MODE OF SLOW SAND FILTRATION FOR WATER TREATMENT IN GUNUNG KIDUL (Case Study in Gua Seropan) - , AGUSTINA KIKY ANGGRAINI, Ir. Agus Prasetya, M.Eng.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Gunung Kidul was indicated as an area with highest vulnerability index of drought disaster. Actually, this problem can be solved by pumping out the water from underground rivers exist there but there was a problem regarding to water quality which does not meet the requirements of any regulatory standard of drinking water. It needs to be treated before used for drinking water purposes. According to IWRM research project, a suitable water treatment for Gunung Kidul was slow sand filtration but that research did not consider the local media (condition of local availability), temperature, raw water quality, and suitable operation mode. Those limitations of previous research became the consideration to conduct this research which focused on finding suitable local media and suitable operation mode. A laboratory experiment divided into two phases, first to find out the suitable local media and second to find out suitable operation mode was conducted. The assessment of the experiment was based solely on the turbidity removal. Test of both phases used PVC columns and artificial turbidity water. The artificial turbidity water was created from the mud of Gua Seropan and tap water and it would be analyzed its comparison with Heilerde (surrogate material) used by previous research whether it was representative or not. Analyses of media characteristics (d10, d30, d60, d90, Cu, and Cc) by doing sieving analyses before they were constructed in the columns were performed. Other parameters measured were specific gravity, permeability, and porosity. On the phase I, five types of local sand (lava sand, beach sand, zeolite sand, activated sand, and silica sand) were tested by doing filtration process. Then two best media were selected to be tested in the phase II to find out the suitable operation mode whether it was continuous mode or intermittent mode. According to the experiments, there were six conclusions which could be concluded. First, slow sand filtration was a suitable water treatment method for Gunung Kidul. Second, Heilerde was not representative as it would create higher value of turbidity compared to the mud of Gua Seropan. Third, suitable local media for slow sand filtration were lava sand and beach sand. Fourth, the effectiveness of lava sand and beach sand was assessed as both were able to reduce inlet turbidity from hundreds to below 1 NTU. Fifth, lava sand would be more effective under low flow rate (0.1 m/h) and for beach sand under high flow rate (0.3 m/h). Sixth, continuous mode (keeping constant water level) indicated better effluent compared to intermittent mode.